DEVELOPING COMMUNICATIVE COMPETENCE IN TEACHING ENGLISH THROUGH TASK-BASED LANGUAGE TEACHING HIGHER EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The development of communicative competence has become a primary objective in English language teaching, particularly in higher education where students are expected to function effectively in academic and professional environments. Traditional language teaching methods often emphasize grammatical knowledge rather than practical communication skills. Task-Based Language Teaching (TBLT) has emerged as an effective pedagogical approach that promotes meaningful interaction and authentic language use. This article explores the role of TBLT in developing communicative competence among university students learning English as a foreign language. The study discusses the theoretical foundations of communicative competence, the principles of TBLT, its implementation in higher education, and its impact on students’ linguistic, sociolinguistic, discourse, and strategic competencies. The article concludes that TBLT provides an effective framework for fostering communicative competence and preparing students for realworld communication.
Keywords: communicative competence, Task-Based Language Teaching, TBLT, English language teaching, higher education, communicative approach, language learning.